Food Application of Orange Seed Powder through Incorporation in Wheat Flour to Boost Vitamin and Mineral Profiles of Formulated Biscuits - Ashiq Hussain; Salah Laaraj; Tusneem Kausar; Aziz Tikent; Hanane Azzouzi; Samina Kauser; Qurat Ul An; Aqsa Iqbal; Saima Akram; Rizwan Nisar; Ayesha Najam; Haya Fatima; et al. (International Journal of Food Science)
The significance of conducting research for its application has been noted as a result of the rising global food production and waste generation. As a result, there is increasing interest in fruits and vegetable seeds that contain bioactive chemicals, such as those that are obtained from orange seeds. In the current work, orange seed powder replaced wheat flour at 0, 2.5, 5, 7.5, and 10% levels, to observe changes in physicochemical features of developed biscuits. Proximate analysis of orange seed powder and wheat flour revealed that orange seed powder has high fat, fiber, protein, and ash contents as compared to wheat flour, whereas moisture contents in wheat flour were high. In developed biscuits, the highest values (percentage) of ash (9.68±0.04), fiber (6.79±0.12), protein (10.42±0.25), and fat (36.90±0.55) were found in biscuits developed with 10% orange seed powder. Orange seed powder was a comparatively good source of both macro and micro minerals, as compared to wheat flour. High contents of selenium (5.32±0.03), iron (2.12±0.05), zinc (3.88±0.12), and manganese (2.25±0.04) mg/100 g, present in orange seed powder, were the prominent findings of this research work, as wheat flours were observed to be deficient in these trace minerals. Contents of calcium, magnesium, potassium, zinc, manganese, zinc, and selenium in control biscuits were found 20.51±0.08, 17.29±0.04, 46.12±0.05, 1.06±0.01, 1.97±0.01, 0.12±0.01, and 0.11±0.01 mg/100 g, respectively, and replacement of wheat flour with 10% orange seed powder increased values of these minerals to 103.90±0.35, 44.35±0.50, 71.29±0.32, 2.59±0.4, 2.75±0.02, 1.31±0.01, and 2.02±0.05 mg/100 g, respectively. Vitamins E and K, which were not detected in wheat flour, were present in orange powder in high amount, whereas B group vitamins, which were also present in wheat flour, were observed in significantly high quantities in orange seed powder. Increment in vitamin A, D, E, K, and B complexes was significant as a result of orange seed powder supplementation, except for vitamins B1 and B2, which were slightly decreased. Sensory evaluation revealed that a 5% replacement of orange seed powder provided good quality biscuits with acceptable colour, flavor, taste, texture, and overall acceptability. Orange seed powder could prove an important ingredient in the baking industry with the potential of promoting the nutritional value of foods.